Home-made poetry as pedagogical tool: an experience from the law classroom - Manley, Stewart (Wiley, 2018)
Since 2012, I have been using home-made poetry to supplement my teaching of trust law. My experience illustrates how English–in this case poetry–can enhance teaching in other fields. Poetry can capture complex concepts in understandable and memorable ways, provide the human context behind abstract principles and increase authenticity in the classroom. The piece includes original teacher and student-written poems, and student feedback on the use of poetry in the classroom. Home-made poetry leverages English’s power of narrative, imagination and language and can enrich any academic field.